Jeszcze włócznia, czy już kopia? Rozważania w kontekście dzieł sztuki europejskiej - Sierosławski, Artur (Acta Universitatis Lodziensis. Folia Archaeologica, 2012)
The lance is an instantly recognizable medieval weapon. It’s the primary weapon of a medieval knights, the primary he uses in battle. But it’s still not clear when the lance appeared. In most publications its appearance is dated to the 12th c. There are no preserved artifacts and the written sources are not clear on this subject. New informations can be drawn from works of medieval art, especially illustrated manuscripts and architectural decorations. For this deliberation I used iconography dated between the 8th and 14th c. There are three characteristics with which we can distinguish the spear and the lance. The first is the construction of the shaft end. The difference between spear shaft and lance shaft is that the lance shaft had a vamplate, a small circular plate. In many publications it can be read, that this plate was made for protecting the hand. This is of course a misunderstanding. It allowed a firmer grip of the shaft upon impact. There was no need to protect the hand during the duel, because knights were trying to hit the head or the torso of their opponents, not the hand. The second way to recognize the kind of weapon is to analyse how the horsemen uses them. The spears were manipulated with one hand. Horsemen were very often attacking by rising the spear over the head and then striking their opponents from above. Lances were used in a quite different way. Horsemen during the attack had the lances under their arms and struck their enemies facing them. These two polearm techniques can be found on medieval representations. The third characteristic is the shape of the spearhead. In many illustrations it is shown very schematically, therefore very often we can’t identify the type of weapon basing on the presentation of the tip. The only exception is the spearhead of type VI (by Nadolski). The characteristic crosspiece attached to (or slightly below) the bush is quite often marked on the illustrations. In these situations we can be sure, that this weapon is a spear. During the 8th–10th c. mounted units undoubtedly utilized spears, there is no argue about that. On every illustration made at that time which shows a mounted warrior armed with a pole weapon, this weapon is a spear. Around the middle of the 11th c. a very important change in the use of polearms occurred. The Bayeux Tapestry which was made around 1068 depicts horsemen using spears in a manner typical for the lance. One of knights represented in the battle scene holds his spear under his arm and hits his opponent in the face. This is an unquestionable evidence that the evolution of the lance started in the 11th, not the 12th c. Of course I don’t suggest, that the army of William the Conqueror was armed with lances, but that the mentioned work of early medieval art is the oldest evidence of the first step in the evolution of polearms. In this context we should look closer at some types of early medieval spearheads, especially of Nadolski’s type IX, which is relatively short, but massive. Could it be a type of an early lance head? In the 12th and 13th c. the shaft of the lance was developed, the weapon became longer and heavier. Knights represented in art from that time always use their polearms by holding them under their arms. Hunting scenes are the only exceptions. In these cases the horsemen uses their weapons holding them I one hand, above their heads. That proves that they’re using spears. Another important source for this discussion is the Manesse Codex, which was written in the first half of the 14th c. A few illustrations depict duel scenes and “portraits” of knights, who were the main characters of poems contented in the Codex. Some of those illustrations are very accurate, with important details clearly visible. Some of the lances represented here have an additional constructional element, a vamplate. As it was written in the beginning, its presence is one of the essential differences separating the lance from the spear. Is it possible to point the exact time when the lance appeared? Medieval iconography can bring us closer to the truth, but it only allows to identify the ante quem dating. Surely, the first step of the evolution of medieval polearms took place before 1066, before the battle of Hastings that is. But to say exactly how long before the battle took place mounted warriors had already been accustomed to the use of spears in a way specific for the lance – this cannot be determined.